Rancang Bangun Difabel Experience Management Learning bagi Anak Berkebutuhan Khusus pada Sekolah Luar Biasa Sasanti Wiyata: Designing Difabel Experience Management Learning for Children with Special Needs at Sasanti Wiyata Special School - Sunani, Avi; Chairil, Augustin Mustika; Al Haromainy, Muhammad Muharrom; Hardiansyah, In Naka Malik; Christianty, Theressa Marry; Waskito, Achmad Derajat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Sasanti Wiyata Special School (SLB) is one of the special schools in Surabaya that has students with special needs. The results from the focus group discussion revealed the partners' issues, namely the lack of utilization of information and communication technology and the insufficient digital learning experiences for children with special needs. This community service activity aims to enhance the partners' skills in using digital-based learning methods and to improve the abilities of students with special needs in utilizing digital technology for learning. The method of implementing this community service is carried out by providing training, assistance, and evaluation of activities. The training and mentoring were measured using pre-tests and post-tests. The pre-tests and post-tests were processed using descriptive statistics, which showed an improvement in the understanding and skills of the teachers in creating, using, and integrating learning materials on the DXML (Difabel Experience Management Learning) platform. This platform serves as a tool that integrates the Learning Management System (LMS) and the Learning Experience Platform (LXP). The advantage (value proposition) of the synergy between the implementation of LMS and LXP is the customizable DXML that can be tailored to the characteristics of children with special needs at SLB Sasanti Wiyata, specifically those who are hearing impaired and intellectually disabled. From this activity, an increase in the skills of teachers and students in using the DXML digital platform was achieved, making the teaching and learning process easier. Therefore, this community service needs to be carried out continuously.